Evolving role of leadership in promoting innovation: An exploratory study of the Indian Information Technology-Business Process Management industry - Dangle, Shailesh (Curtin University, 2022)
This study aims to examine the emerging role of leadership in the innovative Indian Information Technology and Business Process Management (IT-BPM) industry. The research explores the leadership competencies that drive this industry in 4IR. The study identifies leadership competencies and develops a leadership competency framework contextually suitable for Indian IT-BPM organisations to be innovative and competitive. The study contributes to the existing body of literature with leadership competencies related to technology and innovation.